Automated decision support system for selecting the envelope and structural systems for educational facilities. (15th August 2020) - Alshamrani, Othman Subhi; Alshibani, Adel
Abstract: This paper describes the development of an automated decision support system (DSS) to assist school districts in selecting the best envelope and structural systems for new potential educational facilities from two perspectives: sustainability and lifecycle costing (LCC). The system is designed also to assist decision makers to predict the LCC of their potential buildings by means of stochastic and deterministic forecasting models. Four primary criteria are investigated in order to determine LCC: construction cost, running cost (i.e. energy, operation, maintenance, and renovation costs), returned salvage value and associated costs of environmental impact. The data base of the system hosts fourteen structure and envelope types that the system is capable to evaluate while accounting for the uncertainties associated with life cycle cost elements. The developed decision support system utilizes Monte Carlo simulation to assess the cost effectiveness of a total of fourteen green and non-green school buildings. The evaluation and selection processes are augmented by applying the Efficient Frontier method. This decision support system can assist decision makers in minimizing the overall cost of educational facilities by detecting the most attractive possible envelope/structural system, while minimizing greenhouse gas emissions and its associated environmental footprint. The graphical user interface (GUI) of the system is designed for easy data entry and friendly environment. The core models and components of the developed system are described briefly to maintain continuity, while the paper focuses primarily on the application of the deterministic approach for selecting among alternatives. Highlights: Integrated Life cycle costs and sustainability is a powerful measure for system selection. An automated deterministic and stochastic based decision support system is developed applying MAUT and AHP. Specific focus on the selection of envelope and structural systems for educational buildings. Conventional and sustainable concrete, steel, and wood are investigated as system alternatives. Building envelope and structural systems prove to have a very significant impact on sustainability and LCC.